Developing A Database For The Work Of The extension Units (Latakia University Journal -Biological Sciences Series, 2022)
The research aims to create a database for agricultural extension units that can be accessed via the Internet, through which the required agricultural information and data can be managed.The research data collected by the personal interview of agricultural extension agents and workers in extension units in Lattakia governorate in order to identify the records and decouments and how to manage them. The database management system MYSQL was used with the php programming language to build the desired database, by transforming the data from paper form to digtal form in addition to suggesting some records that can help agricultural extension workers and farmers.The results showed that the system achieves several advantages, including: facilitating the work of the extension unit through data storage, processing, archiving and retrieval, the preparation of various statistics, the dissemination of agricultural information and extension bulletins, and linking the extension units with each other in a unified database. The electronic database enables farmers, agricultural extension workers and other beneficiaries to view extension bulletins and agricultural information, and enables the administration and decision-makers to view the statistical data, and follow up on some of the work of the extension units through devices connected to the internet.